The Implementation of a Multiple Intelligences Teaching Approach: Classroom engagement and physically disabled learners - Nayyereh Ghaznavi; Mehry Haddad Narafshan; Massoud Tajadini (Cogent Psychology, 2021)
The present mixed-methods classroom-based study investigated whether the provision of multiple intelligences teaching approach to physically disabled learners could contribute to activating multiple intelligences and have a positive impact on their classroom engagement. To address this issue, three intact classes of 10 Iranian physically disabled learners participated in this study. In so doing, the study utilized an experimental design with 10 participants in the control group and 20 participants in two experimental groups. Drawing on quantitative and qualitative analysis, the results indicate that, over six months, the use of the multiple intelligences teaching approach contributed to a significant improvement in the learners’ multiple intelligences. The implementation was also successful in raising the learners’ classroom engagement. Further, comparing the first language (Persian) & second language (English) multiple intelligences-based instruction, L2 (English) multiple intelligences-based instruction was more effective in fostering physically disabled learners’ multiple intelligences and classroom engagement.